The Beyond the Surface: A Screening-Based Analysis of Family Health, Psychological Well-Being, and Social Support in Student Mental Health - Multahada, Erna; Sombuling, Agnis; Hidayati, Pawestri Mukti; Nuraqmarina, Fatma; Putri, Prahastia Kurnia (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Student mental health is facing a growing crisis, with rising rates of psychological distress and suicide reported among university populations in Indonesia. This study investigates the influence of three key psychosocial factors—family health, psychological well-being, and social support—on student mental health. A total of 140 university students were selected using an accidental sampling technique. Mental health was assessed using the GHQ-28, psychological well-being was measured with the Psychological Well-Being Scale (PWB), social support was evaluated using the Multidimensional Scale of Perceived Social Support (MSPSS), and family health was assessed through the Family Health Scale–Long Form. Data were analyzed using multiple linear regression to determine both the individual and combined effects of the predictor variables on student mental health outcomes. The results revealed a significant combined effect of family health, psychological well-being, and social support on student mental health (p = 0.000, R = 0.620, R² = 38.4%). When examined individually, family health (p = 0.000) and psychological well-being (p = 0.049) were significant predictors, while social support was not (p = 0.405). However, a post-hoc analysis showed that family-based social support had a statistically significant impact on student mental health (p = 0.001). The novelty of this study lies in its holistic approach, which integrates three major psychosocial predictors within a culturally grounded framework while emphasizing the need for university-based mental health screening systems. The findings underscore the critical role of campuses as supportive microsystems in promoting student mental health through preventive strategies, early detection, and responsive programming. Developing a psychologically safe and inclusive learning environment is essential to improving students’ overall well-being.